Driving Bureaucracy Towards Post NPM: Case Studies And TNA Item Bank Management - Nur Muhammaditya; Sudarsono Hardjosoekarto (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
This study aims to analyze the transformation of the New Public Management into the New Public Management within the framework of institutional divergence. The study focuses on the transformation of New Public Management as an institutional phenomenon within the framework of bureaucratic hybridization that results in unique divergences according to the organization. Social actors as the main element of institutional normative coupled with other institutional mimetics have an impact on elaboration patterns of government, affecting efficiency and organization. The case study methodology was chosen to see how the roles of actors in the bureaucracy with the help of Text Network Analysis as a visual and structured confirmation tool. The results show that the hybridization of public management in the bureaucracy needs to go beyond coercive factors to encourage the potential of state apparatus in digital governance towards ideal Post New Public Management. Methodological findings in the form of qualitative research variants that are adaptive to the application of technology can be applied to build strong data validity and reliability. Theoretically, the findings also complement institutional divergence studies that have not yet examined the context of the digital bureaucracy era.